Molecular and Biochemical Insights Into Early Responses of Hemp to Cd and Zn Exposure and the Potential Effect of Si on Stress Response - Luyckx, Marie; Hausman, Jean-François; Sergeant, Kjell; Guerriero, Gea; Lutts, Stanley (Frontiers in Plant Science, 2021)
With the intensification of human activities, plants are more and more frequently exposed to heavy metals. Zinc and cadmium are frequently simultaneously found in contaminated soils, including agronomic soils contaminated by atmospheric fallout near smelters. The fiber crop Cannabis sativa is a suitable alternative to food crop for cultiavtion on these soils. In the present study Cd (20 µM) and Zn (100 µM) were shown to induce a comparable growth inhibition in Cannabis sativa. To devise agricultural strategies aimed at improving crop yield, the effect of silicon (2 mM Si) on plants’ stress resistance was considered. Targeted gene expression and proteomic analysis were performed on leaves and roots after one week of treatment. Both Cd and Zn stimulated genes involved in proline biosynthesis (P5CR) and phenylpropanoid pathway (PAL) but Cd also specifically increased the expression of PCS1-1 involved in phytochelatin synthesis. Si exposure influence the expression of numerous genes in a contrasting way in Cd- and Zn-exposed plants. At the leaf level, the accumulation of 122 proteins was affected by Cd while 47 proteins were affected by Zn: only 16 proteins were affected by both Cd and Zn. The number of proteins affected by Si exposure (27) alone was by far lower and 12 of them were not modified by heavy-metal treatment and no protein appeared to be modified by both Cd/Si and Zn+Si treatment. It is concluded that Cd and Zn had a clear different impact on plant metabolism and that Si confer a specific physiological status to stressed plants with quite distinct impact on hemp proteome depending on the considered heavy metal.